Enhancement of confined femto-ablation at SiO2/Si interface by embedded metallic nanoparticles - Rehman, Zia Ur; Na, Le T.; Tan, Chee Leong; Irfan, Muhammad Abeer; Qayyum, Abdul; Janulewicz, Karol Adam (Elsevier, 2018)
Influence of doping an SiO 2 /Si interface with metallic nanoparticles (MNPs) on confined laser ablation and resulting structural properties of the crystalline silicon (c-Si) substrate was investigated by irradiating the composed interface with a single, tightly focused femtosecond laser pulse. Confinement ablation regime was enforced by a 10 μm–thick SiO 2 layer capping the c-Si substrate. A mixture of gold (Au) and silver (Ag) nanoparticles was placed at the interface to take advantage of the presumed plasmon-induced enhancement of the incident field strength in a broad spectral range. The nanoplasmonic effect is visualised by numerical simulations utilising the mathematical apparatus of the finite-difference time-domain (FDTD) method. The structural transformations at the site of the laser-induced damage were investigated dominantly by the scanning (SEM) and high-resolution transmission (HRTEM) electron microscopes. A comparative analysis of the irradiation effects in the targets containing different combinations of the interface composing elements revealed clear and strong influence of the confinement and doping on the irradiation result. Character of the observed transformations (among others the crystal twinning) suggests dominant role of increased pressure in the process through the locally generated shock waves.